Simplification of Home Automation System Using Various Sensors, Actuators and Control System - Rawal, Shannay; Ramachandran, M; Fegade, Vishal; Ragavendran, U (International Journal of Engineering and Technology, 2018)
Usually, home automation talks about the domestic atmosphere that increases the class of the occupantâ€™s life by eliminating as much human interface as in theory possible in numerous domestic practices and exchange them with automated mechatronics systems. Home automation comprises selected form of intelligence, home network and or centralized or logic distributed network or specific control unit. The modest system works on an approach in which the functionality is hardwired and incorporated into the system and cannot be altered automatically without the interference of technical or a knowledgeable person. Advanced sensor technology with Wireless advancement expands our sensing competencies by linking communication networks and physical world which enables wide-ranging applications in respect of home automation. In this article, we are discussing various sensors, actuators and control systems utilized for the home automation systems.Â Â